CAREER DEVELOPMENT AND MOTIVATION: A STUDY ON STRENGTHENING ORGANIZATIONAL COMMITMENT IN ISLAMIC EDUCATIONAL INSTITUTIONS - Irawan, Feri Indra; Nugraha, Heru; Hamidah, Euis Erha Rohmah; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the influence of career development on organizational commitment which is mediated by the work motivation of teaching and education staff in Islamic educational institutions. The problem of low organizational commitment in this context is thought to be related to less than optimal career development programs that do not fully consider motivational aspects. Using a quantitative approach, data was obtained from 100 respondents who met the inclusion criteria, then analyzed using the path analysis method with the help of the SmartPLS application. The research results show that career development has a significant direct influence on organizational commitment. In addition, work motivation was found to act as a mediator that strengthens the relationship between career development and organizational commitment. This finding is in line with Herzberg's motivation theory which emphasizes the importance of motivator factors in supporting individual and organizational performance. In the context of Islamic educational institutions, work motivation influenced by Islamic values is an important element in building strong organizational commitment. This research contributes to the development of literature by integrating these variables in a unique context, namely Islamic educational institutions. The practical implication of this research is the need for managers of Islamic educational institutions to design holistic and motivation-based career development programs to increase the organizational commitment of teaching and educational staff.